Managing Side Effects of Cytotoxic Chemotherapy in Patients With High Grade Gliomas - Ha, Hyerim; Lim, Joo Han (Brain tumor research and treatment, 2022)
Cytotoxic chemotherapy has been a mainstay of cancer treatment since the 1940s. In the recent era of emergent targeted therapies and immunotherapies, many cytotoxic chemotherapy agents including temozolomide are still one of main weapons for the treatment of high grade gliomas. However, cytotoxic chemotherapy often causes side effects. Proper management of chemotherapy-induced toxicity can have a significant impact on a patient's quality of life and clinical outcomes. Many supportive care advances have transformed our ability to give full doses of chemotherapy, which is important for achieving their full efficacy. Prevention and treatment strategies have been developed for many chemotherapy-related toxicities. This review focused on managing gastrointestinal toxicity, chemotherapy-induced nausea and vomiting, and hematologic toxicities such as thrombocytopenia during cytotoxic chemotherapy treatment in high-grade brain tumors.